The Influence of Marketing Mix Strategies on Purchase Decisions For Bambo Charchoal Products (Study on Management Department Students, Feb Unismuh Makassar). - Nurul khotimah; Ruliaty, Ruliaty; Aulia, Aulia (International Journal of Economic Research and Financial Accounting, 2024)
This study aims to determine and analyze the effect of Marketing Mix Strategy on Purchasing Decisions for Bambo Charcoal Products (Study on Students of the Management Department of FEB Unismuh Makassar). The type of research used in this research is descriptive quantitative. The population in this study were students majoring in management at Unismuh Makassar. The sample used in this study were 76 respondents. Data collection techniques using questionnaire techniques. The data analysis technique used to test the hypothesis is multiple linear regression and t test (partial test) which is processed using statistical calculations through the Statistical Package for the Social Science (SPSS) version 26. The results showed that the description of Product, Price, Location and Promotion had a positive and significant effect on the decision to purchase Bambo Charchoal products.